Factors Related to Exclusive Breastfeeding Behavior for Toddlers - Septi Ariyanti, Yeni; Handayani, Rini; Heryana, Ade; Cempaka Putri, Eka (Rifa'Institute, 2023)
Introduction: Breast milk is one of the best investments to meet nutritional needs and optimize children's survival in the first two years. Various studies have proven the influence of breast milk. Breastfeeding also affects the level of intelligence and provides protection against various diseases in the future, such as overweight and diabetes. The coverage of exclusive breastfeeding in the Bina Sejahtera VII Panunggangan Integrated Healthcare Center work area is only 47%. The coverage value is not in accordance with the target standard of the Indonesian Ministry of Health, which is 80%. Objective: Knowing the factors related to exclusive breastfeeding behavior for toddlers in the work area of Integrated Healthcare Center Bina Sejahtera VII Panunggangan Pinang Tangerang City in 2023. Method: The type of research is quantitative research with a cross-sectional research design. Result and Discussion: There is a relationship between education (p-value = 0.031), with exclusive breastfeeding behavior and there is no relationship between attitude (p-value = 0.436) and husband support (p-value = 0.979) with exclusive breastfeeding behavior for toddlers in the Bina Sejahtera VII Panunggangan Pinang Integrated Healthcare Center working area in Tangerang City in 2023. Conclusion: It is expected that counseling and coaching programs are carried out regularly and optimally not only for mothers but also for couples (husbands) to support the achievement of exclusive breastfeeding targets.